2011
DOI: 10.1162/jocn.2011.21612
|View full text |Cite
|
Sign up to set email alerts
|

Network Dynamics Mediating Ipsilateral Motor Cortex Activity during Unimanual Actions

Abstract: Abstract■ Executing difficult actions with the left hand results in bilateral activity of motor areas along the precentral gyrus. Using TMS and fMRI, we explored the functional relationship between primary (M1) and premotor areas during unimanual actions, focusing on M1 activity in the ipsilateral hemisphere. Single-pulse TMS revealed that the amplitude of motor-evoked potentials (MEPs), elicited in the stationary right-hand muscles following left M1 stimulation, fluctuated with the state of homologous muscles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 51 publications
(99 reference statements)
6
41
0
Order By: Relevance
“…Although we correctly hypothesised an increase in contralateral synergist muscle strength, we thought (incorrectly) this would be accompanied by increased corticomotor excitability projecting to the untrained synergist wrist flexors. This hypothesis was based on well-established evidence, that unilateral voluntary contractions not only activate the contralateral motor pathway, but also the ipsilateral motor pathway targeting the resting or untrained limb Hortobágyi et al 2003;Ruddy et al 2017;van Duinen et al 2008;Perez and Cohen 2008;Verstynen and Ivry 2011;Carson and Ruddy 2013;Hendy and Kidgell 2014;Zult et al 2016). On this basis, it was likely that the untrained synergist wrist flexors would experience increased excitability following training, because of its isometric role in the strength training protocol and because of the contribution of shared corticospinal inputs between agonists and synergists (Smith and Fetz 2009;Capaday et al 2013).…”
Section: Corticomotor Excitability Is Spatially Confined To the Untramentioning
confidence: 99%
“…Although we correctly hypothesised an increase in contralateral synergist muscle strength, we thought (incorrectly) this would be accompanied by increased corticomotor excitability projecting to the untrained synergist wrist flexors. This hypothesis was based on well-established evidence, that unilateral voluntary contractions not only activate the contralateral motor pathway, but also the ipsilateral motor pathway targeting the resting or untrained limb Hortobágyi et al 2003;Ruddy et al 2017;van Duinen et al 2008;Perez and Cohen 2008;Verstynen and Ivry 2011;Carson and Ruddy 2013;Hendy and Kidgell 2014;Zult et al 2016). On this basis, it was likely that the untrained synergist wrist flexors would experience increased excitability following training, because of its isometric role in the strength training protocol and because of the contribution of shared corticospinal inputs between agonists and synergists (Smith and Fetz 2009;Capaday et al 2013).…”
Section: Corticomotor Excitability Is Spatially Confined To the Untramentioning
confidence: 99%
“…Existing literature reported that primary motor cortex ipsilateral (M1 ipsi ) to the active limb is active during unilateral movement (Bütefisch, et al, 2014;Chiou, et al, 2014;Hinder, et al, 2010;Howatson, et al, 2011;Kim, et al, 1993;Lee, et al, 2010;McMillan, et al, 2006;Verstynen & Ivry, 2011). To understand the movement representation of the activity in M1 ipsi , we first examined the timing and the coordinate frames of movement that is represented in the M1 ipsi to the active limb in Chapter 2.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…Neural adaptation induced through experience by unilateral training could be encoded in a neural network that is responsible for use-dependent learning in both hemispheres and is accessible by the untrained limb (Carroll, et al, 2014;Verstynen & Ivry, 2011;Verstynen & Sabes, 2011). Accessibility of the information by the untrained limb could be brought about via the corpus callosum because of massive connections between hemispheres (van der Knaap & van der Ham, 2011;Wahl & Ziemann, 2008).…”
Section: Possible Mechanisms For Transfer Of Use-dependent Learning Ementioning
confidence: 99%
See 2 more Smart Citations